Is China approaching the inflection point of the ecological Kuznets curve? Analysis based on ecosystem service value at the county level. (15th January 2023) - Pan, Yuling; Dong, Feng; Du, Congcong
Abstract: Accounting for the ecosystem service values (ESVs) and discussing the relationship between the ESVs and economic development can help achieve sustainable ecological development. Therefore, this paper evaluates the county-level ESVs of various land types in China, and depicts the distribution of ESVs in various urban agglomerations. In addition, the nonlinear relationship between ESVs and economic development is revealed. The main findings are as follows: (1) From 2000 to 2018, the ESVs in China decreased, and the decline rate of ESVs in urban agglomerations is much higher than that of China as a whole. (2) The decline rate of ESVs in core cities is much higher than in urban agglomerations, and the decline rate of ESVs is higher in areas close to core cities and lower in areas far from core cities. (3) The ecological Kuznets curve of China has a positive "U" shape, and the ecological Kuznets curve of urban agglomerations has an "N" shape; the ecological Kuznets curve of core cities has a positive "U" shape, while the ESVs of other cities decreases monotonically with the increase of the economic level. Highlights: This paper fills the data gap of ESVs at the county level in China. The reduction rate of ESV in urban agglomeration is larger than the national level. The reduction rates of ESV in core cities are larger than the urban agglomerations. The ecological Kuznets curve is "U"-shaped in China. Non-urban agglomeration cities are still left to the inflection point.